ОЛИЙ ПЕДАГОГИК ТАЪЛИМ МУАССАСАЛАРИДА МОЛЕКУЛЯР ФИЗИКАНИ КРЕДИТ–МОДУЛЬ АСОСИДА ЎҚИТИШ МЕТОДИКАСИ - Избосаров, Б.Ф.; Камолов, И.Р.; Канатбаев, С.С. (SCIENCE and SOCIETY, 2021)
This article reveals the theory and methodology of teaching molecular physics in a credit-modular system in higher pedagogical institutions. Also the completed concepts of the module, their goals and objectives in education are introduced in this article.